Internalization of Personal Hygiene and health in Early Childhood in the School and Family Environment - Sutiyah Nova Irawati; M Haidar (Universitas Negeri Padang, 2023)
The purpose of this study is to provide an overview and strategies that can be carried out by teachers and parents in fostering children to maintain cleanliness and health. This research uses a qualitative approach and literature study. The data sources for this research are teachers and parents at the Cemerlang Insan Early Childhood Education Institute in Magetan and literacy studies that come from relevant studies. The results of this study indicate personal hygiene and health activities carried out at PAUD Insan Cemerlang Magetan consist of three parts, namely (1) Self-cleaning, (2) Consumption of nutritious food, and (3) Optimization of children's motor functions. Aspects of self-cleaning are carried out with several activities such as washing hands and feet, bathing, keeping hair and mouth clean. In the aspect of consumption of nutritious food, a balanced nutritional diet is carried out which prioritizes meeting the nutritional needs of children. Furthermore, to optimize children's motor function through regular exercise. Internalization of personal hygiene and health is carried out collaboratively by teachers and parents through three ways, namely habituation, setting an example and supervision.